The chinese 'go global' policy and the portuguese kinship - Ilhéu, Fernanda (2012)
With the objective of promoting trade and investment and implement common projects in various domains between China and Portuguese-Speaking Countries (PSCs), the Forum for Economic and Trade Cooperation was created by the Chinese government in 2003. This Forum based in Macao, follow the theoretical rational that internationalization is largely driven by networks of relationships, very often based in a share culture and language and that the network relationships of a firm is capable of providing the context for its international activities. Being part of the soft power diplomatic approach to the Portuguese Speaking Countries - considering that some of these markets are very important for Chinese economic development, due to the need to expand its foreign markets and, most importantly, to guarantee the supply of critical raw-materials and sources of energy - this charm offensive utilizes as persuasive tools the cooperation for development, humanitarian aid, cultural ties, bilateral and multilateral diplomacy, and the OFDI. In order to be effective, this model of global cooperation requires that every participant perceives it as being mutually beneficial, i.e., a “win-win” situation for all. Therefore to be a positive contributor to the Chinese “Go Global” policy this Portuguese kinship network should have the perception that Macao Forum activities contribute to the development of its business objectives - increase exports, investment growth, and other business with positive economic results - with China, Macao and between themselves. Our research was aimed at Portuguese companies (exporting and/or investing in China, Macao and HK) in order to get a clearer idea of their opinion about their perception of the Forum and its potential. Within this set of conclusions, we can consider that Macao Forum can do better for the perception of positive benefits for the Portuguese companies participating in its activities thus creating the perception of a “win-win” situation, reinforcing its utility in the increase of exports to China, growth of FDI in China, Macao and PSCs, the increase of business networks between companies of these economic spaces and the increase of business economic results in other kind of business rather than exports or investment. In the future we intend to conduct similar research on the perceptions of companies of other PSCs.